Al-Qadi Abu Ya‘la’s doctrine of the imamate: approach and methodology - Abdul Azeez, Yusuf; Ansari, Abdul Haseeb (Serials Publications, 2011)
The main objective of this paper is to examine the Islamic system of government, which in classical terminology is known as the imamate according to the view of al-Qadi Abu Ya‘la as well as the approach and methodology adopted by him. His doctrine approach on imamate is quite unique, germane, and well-focused in the sense that he harmonized and codified the views of the Hanbali Madhhab on the Islamic system of government and constitutional theory. Al-Qadi Abu Ya‘la’s great contribution to the constitutional and legal theories is that he gave detailed accounts of the administrative machinery of government and transformed the norms of governance into a viable framework.